Bosnia and Herzegovina : Technical Assistance Report-Government Finance Statistics Diagnostic Mission-Institutional Units and Public Sector Debt. (IMF Staff Country Reports; Country Report ;, 2018)
This Technical Assistance Report assesses the current government finance statistics compilation environment in Bosnia and Herzegovina (BiH), particularly the classification of institutional units and debt data compilation based on the Government Finance Statistics Manual and European System of National and Regional Accounts frameworks. It was found that a full list of public sector units in BiH does not currently exist. The Central Bank of Bosnia and Herzegovina (CBBH) is in a good starting position to compile the public sector debt data. The results of its work on financial balance sheets should enable the CBBH to produce general government debt data in a relatively short term.